O modlitwach w Podróży do Świętych miejsc w 1830 roku Andrzeja Murawjowa - Kościołek, Anna; Szulc, Arleta (Przegląd Wschodnioeuropejski, 2024)
Conversation with God accompanied people of various times, nations and religions, because of a universal dimension of the desire for dialogue with the Absolute. The article attempts to analyze those of the prayers which Andrey Muravyev, a Russian writer, poet, state and church activist, practiced during his first pilgrimage to Palestine. Texts of the prayers were from The journey to Holy Places in 1830 (2 vols), which is a record of the author’s experiences and impressions from his pilgrimage to the Holy Land. As an epigraph to both parts of this Muravyev’s work, the words from Ps 135(134) – a hymn of praise to the Lord who works miracles – were served. Attention of the article is paid to: the sense of the prayers, their biographical and literary context, the lexical and partly grammatical material, which Muravyev used (making necessary reference to the Greek and (or) Hebrew sources of Church Slavonic translations of the prayers) and their theological message as well.